Bernardo Bátiz-Lazo, J. Carles Maixé-Altés y Paul Thomes (Eds.): Technological Innovation in Retail Finance. International Historical Perspectives. Nueva York, Routledge, 2011, 319 págs. - Ortiz-Villajos, José María (Investigaciones de Historia Económica, 2019)
Sin resumen